The Relationship between language proficiency, metacognitive awareness, critical thinking disposition and critical reading disposition and critical reading ability among Malaysian ESL undergraduate - Mohd Zin, Zuhana (2014)
This study explored the influence of language proficiency, metacognitive awareness and dispositional attributes in critical thinking and reading on critical reading ability among Malaysian ESL learners. The participants were 295 ESL students. This study adopted a mixed method design in that a correlational analysis was conducted to investigate the relationship between the variables, and a text analysis was conducted to triangulate the findings of the students’ critical thinking and reading dispositions with the critical reading skills. This study utilised Oxford Proficiency Test (OPT),Metacognitive Awareness and Second Language Reading (MA), California Critical Thinking Disposition Inventory (CCTDI), Critical Thinking Disposition Inventory (CTDI) and Critical Reading Comprehension Test (CRCT). The results of the quantitative analysis indicated that the level of the students’ critical reading skills ranged between poor to average. They students lacked the skills to perform in reading and thinking skills that measure evaluation and analysis ability. Further, the levels of their overall critical thinking and reading dispositions, and metacognitive awareness were average. The correlational and the analysis showed that language proficiency was the factor that related and predicted the students’ ability to read critically. In the qualitative method, the students’ written responses to the open-ended comprehension questions in the CRCT were analysed according to identified themes of critical reading skills: understanding, analysis and evaluation. Even though critical thinking and reading dispositions were not significantly related to critical reading skills, a consistent thinking and behavioral patterns were identified among the students in their written responses to the comprehension questions. They evidently lack the reasoning and inference thinking skills. It can be concluded that they also lacked the suspending judgment and questioning attitude when they read. In addition, the analysis of the written responses indicated that the students were not able to metacognitively aware of the strategy to repair comprehension failure during reading. The findings of the study showed the students were less able to read critically and their ability was significantly related to language/proficiency in L2. The findings of the written responses also indicated that critical thinking and reading dispositions played a part in contributing to their poor critical reading ability. The students’ low level of proficiency in English could have contributed to the overall findings of the study particularly to poor performance in the CRCT because most of the students in the study were represented by low proficiency students. The results of the study have implications for the reading instructions among ESL learners in Malaysia in that teachers and student teachers alike need to be aware of the factors and provide explicit critical thinking and reading dispositions to the students.